Regulierung im Telekommunikationssektor Chancen und Risiken im historischen Prozess - Schmoeckel, Mathias; Michalczyk, Roman; Kurth, Matthias (Mohr Siebeck, 2012)
Regulation in the Telecommunications Sector. Opportunities and Risks in a Historical Process.
PublicationDate: 20210517
Keywords: Rechtsgeschichte -- Telekommunikation -- Regulierung -- Wirtschaftsgeschichte -- Allgemeines -- Array